Exploration and study of polarimetric ground penetrating radar imaging - Shao, TIanji (2016)
Ground Penetrating Radar (GPR) is a nondestructive method using electromagnetic radiation to detect the subsurface structure. The principle is that when EM wave reaches the surface of a subsurface object, it will interact with the object and gets scattered in all directions. The radar system captures the part of the scattered wave that is directed back towards the receiving antenna. As a result of the interaction with the target, the properties of the reflected wave change and therefore can be different from the incident one. Those changes in reflected wave will thus carry information about polarimatric scattering properties of the target object. Thus, by controlling the polarization of the incident wave and measuring the full polarization of the backscattered wave, the radar system can be used to learn more about the target. This project aims to integrate a simple GPR system using laboratory equipment and to detect some simple subsurface objects (such as soil, sands, rock, voids) and study their correlation between GPR data/images and the tested subsurface objects. Polarimetric Synthetic Aperture Radar (PolSAR) is used in the experiment as GPR. The report will first review the underlying principle of radar system, polarization in particular. Then experiment setup and process will be depicted. In addition, various decomposition methods which are used to analyze the PolSAR data will be introduced and in the end results will be shown.